Analysis of Jinayah Fiqh on Adultery and the Moral Damage of the Younger Generation - Abdul Hakim; Annisa Putri Sinaga; Vressillia Witama; Irpan Mauliandi Damanik; Arsyad Rizki Pratama (ISNU Sumatera Utara, 2024)
Adultery is viewed in Islamic law as an act that not only violates moral norms but also has broad legal and moral implications, especially for the character formation of the younger generation. The weakening of moral awareness due to the normalization of sexual relations outside of marriage raises concerns about the destruction of the value system protected by Islamic law. This article aims to examine the views of Islamic jurisprudence (fiqh jinayah) on adultery as a crime, its impact on the moral decay of the younger generation, and the purpose of establishing sanctions for adultery as a preventive measure. The research method used is normative legal research with a fiqh jinayah approach. The approaches applied include a normative Islamic regulatory approach (statute approach) through a study of the Qur'an and Hadith, and a conceptual approach (conceptual approach) by examining the thoughts of Islamic scholars regarding adultery and its punishment in Islamic criminal law. The research data sources are secondary legal materials obtained through literature studies, including fiqh jinayah books, Islamic criminal law books, scientific journals, and the opinions of relevant Islamic legal experts. Data analysis is conducted qualitatively by interpreting and constructing Islamic legal norms to obtain a comprehensive understanding. The results of the study show that jinayah fiqh views adultery sanctions as an instrument for maintaining morals and protecting society, which is directed at preventing the spread of moral damage, especially among the younger generation.